Pengaruh Tingkat Religiusitas dan Pemahaman Asuransi terhadap Keputusan Bernasabah Asuransi Jiwa Syariah - Daud; Ahmad Edi Saputra; Susanti, Pini; Mulyana (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2024)
This study aims to elaborate on the influence of religiosity and the level of understanding of Sharia insurance on the decision to become a Sharia insurance policyholder. The research was conducted using a quantitative approach with multiple linear regression. The findings reveal that the decision of customers to use Sharia insurance increased by 4.544%, even without changes in other independent variables such as religiosity and understanding. Religiosity was found to have a positive influence, contributing to a 40.4% increase in decisions, while increased knowledge related to Sharia insurance products had a positive impact of 40.8%. The SPSS analysis results indicate that 80.6% of the variation in customer decisions can be explained by these two variables, while the remaining 19.4% is influenced by other factors not included in the regression model. This study highlights that both religiosity and knowledge play crucial roles in influencing customer decisions to choose Sharia insurance, but external factors should also be considered for a more comprehensive understanding.